Design and implementation of a SHA-3 candidate Skein-512 hash/MAC hardware architecture - Michail, Harris; Athanasiou, George S.; Tsingkas, Elias N.; Chalkou, Chara I.; Theodoridis, G.; Goutis, Costas E. (My University, 2012)
Many cryptographic primitives that are used in crucial cryptographic schemes and commercial security protocols utilize hash functions. Recently, the National Institute of Standards and Technology (NIST) launched an international competition for establishing the new hash standard, SHA-3. One of the semifinalists is the Skein algorithm. In this paper, an 8-round unrolled architecture of the complete Skein algorithm is presented, implemented in Xilinx Spartan-3 and Virtex-5 FPGAs. The design is able to perform both as simple Hash and MAC module. The performance metrics, such as Frequency and Area, that are gathered, show that the proposed implementation is more efficient in terms of Throughput/Area, compared to other similar ones, proposed by academia.
Keywords: Cryptography; Algorithms; Hardware